2015
DOI: 10.1586/14760584.2015.1061938
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of two novel DNA vaccines expressingToxoplasma gondiirhomboid 4 and rhomboid 5 proteins against acute and chronic toxoplasmosis in mice

Abstract: The pVAX-TgROM5 showed a better protective efficacy against acute and chronic toxoplasmosis compared to pVAX-TgROM4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…The immunization of mice with pDsRed2-GRA8 could induce significantly higher levels of IgG antibodies than those in the controls ( P <0.05), which would contribute to strong protective efficacy against T. gondii infection. These results were in agreement with those of previous studies that vaccinated mice with plasmids encoding GRA7, GRA17, GRA23, ROM5, and ROP38 [ 10 , 26 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The immunization of mice with pDsRed2-GRA8 could induce significantly higher levels of IgG antibodies than those in the controls ( P <0.05), which would contribute to strong protective efficacy against T. gondii infection. These results were in agreement with those of previous studies that vaccinated mice with plasmids encoding GRA7, GRA17, GRA23, ROM5, and ROP38 [ 10 , 26 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that the onset of symptoms were later in immunized mice, which had prolonged survival times and reduced brain cysts compared with negative controls. Zhang et al [38] constructed a pVAX-TgROM4 DNA vaccine and evaluated the immunogenicity in Kunming mice. They showed that the TgROM4 DNA vaccine induced strong humoral and cellular responses and was a potential vaccine candidate against toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were collected after clot retraction and were stored at –80°C until analysis. The total and subclasses of anti- T. gondii IgG antibodies as an indicator of Th1 and Th2 responses were determined by ELISA as previously described (30, 31). Briefly, wells of 96-well microtiter plates were coated with 100 µl (10 µg/ml) STAg (diluted in PBS) and were incubated at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%